Study of small ions concentration in the air above Athens, Greece - Retalis, A.a; Nastos, P.b; Retalis, D.a (Atmospheric Research, 2009)
Measurements of positive and negative small atmospheric ion concentrations have been made regularly since 1968 at the National Observatory of Athens (NOA). In this paper the 17-year period 1968-1984 is summarized. The diurnal and annual variations are examined, and Fourier analysis is also used for the study of the diurnal variation. The concentrations of small ions follow a double diurnal course. The maxima occur near 3-5 h and 13-16 h local time (LT = GMT + 2 h). The minima are observed at 6-8 h and 21-23 h. The annual course of small ions presents maximum concentration values around the summer season. The mean of the small ion concentration (SIC) for the 17-year period (1968-1984) is n+ = 188.8 ions/cm3 for positive ions and n- = 151.1 ions/cm3 for negative ions. Their ratio is equal to 1.25. The year-to-year variation of SIC for the examined period shows a negative trend. The results from multiple regression analysis show that wind speed and SIC are positively correlated, while relative humidity, smoke and sulphur dioxide are negatively correlated. © 2008 Elsevier B.V. All rights reserved.
Keywords: Air pollution; Air quality; annual variation; Athens; Athens [Attica]; Atmospheric electricity; Atmospheric humidity; Atmospherics; Attica; diurnal variation; Eurasia; Europe; Forestry; Fourier analysis; Greece; ion; Ions; Meteorology; Moisture; Regression Analysis; Relative humidity; Small ions; Smoke; Southern Europe; Sulfur; Sulfur determination; Sulfur dioxide; Sulphur dioxide; Turbulent flow; Wave interference; Wind effects; Wind speed; wind velocity